PENERAPAN MEDIA GAME KAHOOT TERHADAP HASIL BELAJAR MATEMATIKA DiSEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Widya Pratiwi Nawawi; Berta Apriza; Purna Bayu Nugroho (Journal for Lesson and Learning Studies, 2025)
Many students experience difficulties and show low interest in learning mathematics. One possible solution to enhance students’ motivation and engagement is the use of interactive quiz-based game media such as Kahoot. This study aims to analyze the effectiveness of Kahoot in improving elementary school students’ mathematics learning outcomes. The method employed is a systematic literature review by examining scholarly articles published between 2020 and 2024, obtained through Google Scholar searches. From a total of 18,700 articles identified, a screening process based on inclusion criteria was conducted, resulting in 10 articles selected for review. Data were analyzed using a descriptive qualitative approach. The findings indicate that Kahoot is effective in strengthening the understanding of basic mathematical concepts and increasing students’ learning motivation. However, several limitations were identified, including unequal access to technology and students’ tendency to focus more on competition rather than comprehension of the material. Overall, the implementation of Kahoot creates enjoyable and interactive learning experiences, contributing positively to the improvement of mathematics learning outcomes. The implications of this study highlight that integrating interactive digital media into the learning process can enrich teaching strategies, although challenges related to technology access need to be addressed in future implementations.